2010
DOI: 10.1111/j.1365-2672.2009.04584.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of survival ofListeria monocytogenes,SalmonellaInfantis andEnterococcus faecalisartificially inoculated into experimental waste or compost

Abstract: Aims:  To evaluate survival of pathogenic strains, Listeria monocytogenes and Salmonella Infantis and a sanitation indicator Enterococcus faecalis in composts at different stages of the composting process and during storage. Methods and Results:  The studied pathogenic and indicator strains, originally isolated from compost, were inoculated into compost samples from the various stages of the composting process. During incubation, indigenous microflora diversity was monitored with DGGE analysis. After 90 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Competition between microorganisms within compost piles may also increase microbial diversity, potentially providing ecological niches for pathogen regrowth (Paniel et al, 2010). Microorganism diversity within compost piles has a direct effect on the biological activity and soil microbial community when manure‐based compost is applied (Wang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Competition between microorganisms within compost piles may also increase microbial diversity, potentially providing ecological niches for pathogen regrowth (Paniel et al, 2010). Microorganism diversity within compost piles has a direct effect on the biological activity and soil microbial community when manure‐based compost is applied (Wang et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…one of the three aforementioned pathogens. Compost at the week 8 stage also showed greater microbial diversity than composts aged 0 to 6 weeks, indicating that the diversity of mesophilic organisms present in the cooling stage may have inhibited pathogen growth and survival (59). Other studies have shown that S. Typhimurium growth was significantly greater in composted biosolids which had been sterilized than in nonsterilized composted biosolids, indicating that indigenous microorganisms play a role in inhibiting S. Typhimurium growth (65).…”
Section: Microbial Competition Inhibiting Pathogen Growth In Compostmentioning
confidence: 91%
“…No single physicochemical factor was able to predict if a compost sample could support the regrowth of pathogens; however, moisture content, C:N ratio, and total organic carbon levels were the three physicochemical factors which contributed the most to the regrowth potential of pathogens in finished compost. Other reports support the difficulty in identifying a single physicochemical factor which can predict resuscitation of pathogens in compost (59). Increased relative humidity (percent moisture), has been shown to prolong bacterial survival in finished composts.…”
Section: Resuscitation/regrowth Of Pathogens In Compostmentioning
confidence: 98%
See 1 more Smart Citation
“…Generic Escherichia coli indicator levels are currently monitored to ensure the safety of produce; however, the persistence of Salmonella on the surfaces of peaches, cantaloupes, lettuce, and bell peppers has been shown to be very different from that of E. coli (9,10). In general, Salmonella survives better outside of its animal hosts than E. coli (11) and can persist in processed organic waste and amended soils better than fecal coliforms, although its persistence appears to be strain and/or site dependent (12)(13)(14).…”
mentioning
confidence: 99%